(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The principle of success in the process of learning a foreign language is the most important principle and condition for constantly maintaining interest in learning a subject. This is all the more important when teaching a foreign language in ASO conditions, when the loss of motive due to failure harms the learning process as a whole. However, it should be noted that the ASO model itself, when used correctly, always guarantees the successful formation of communicative competence, since the density of work simply makes it impossible to fail.